Functionalized naphthalenediimide based supramolecular charge-transfer complexes via self-assembly and their photophysical properties. Issue 8 (10th February 2021) - Rani, Pooja; Husain, Ahmad; Shukla, Ananya; Singla, Neha; Srivastava, Ankit Kumar; Kumar, Gulshan; Bhasin, K. K.; Kumar, Girijesh
Abstract : Two new intermolecular CT complexes having large Stokes shift (>170 nm) and significant fluorescence life-time (∼1.55 ns) have been prepared and exploited for cell imaging application. Abstract : We report here the design and syntheses of a naphthalenediimide (NDI)-N functionalized organic fluorophore, 1, and its supramolecular CT complexes [(1 ·2H) 2+ ·(PA − )2 ] (2 ) and [(1 ·2H) 2+ ·(3, 5-DNSA − )2 ] (3 ), self-assembled from 1 as an electron acceptor (A) and picric acid (PA) or 3, 5-dinitrosalicylic acid (3, 5-DNSA) as a donor (D), with a very large Stokes shift (>170 nm) and significant fluorescence lifetime (∼1.55 ns). NDI is functionalized with phenylpyridyl units (chromophore) to extend the π-conjugation and thus provide a suitable platform for strong C–H---π and π⋯π stacking interactions, which are the prime requirements for any compound to be used as a fluorescent probe. The organic fluorophore, 1, and its supramolecular CT complexes 2 and 3 exhibit decent electronic properties as suggested by DFT, cyclic voltammetry, and fluorescence studies. Moreover, compounds 1–3 were also exploited as fluorescent probes for cell imaging under normal cell isolation and with time-bound exposure.